Effects of Malaysian medicinal plants on macrophage functions in vitro study - Al-Bayaty, F.H.; Mohamed, M.A.A.; Abu Hassan, I.; Hussein, S.F. (Academic Journals, 2010)
The effects of aqueous leaf extract of eight local medicinal plant species on the phagocytic and antibacterial potential of mouse peritoneal macrophages against Staphylococcus aureus were investigated. The mouse macrophages cultures were incubated with various concentrations (0.2, 0.4, 0.8, 1.6 and 3.2 mg/ml) of plant extracts in different sets of test tubes at 37 C for one hour. After incubation, their phagocytic and antibacterial effects on S. aureus were determined. Results have shown that the extracts of Orthosiphon stramineus, and Andrographis paniculata inhibited the phagocytic activity and intracellular killing of S. aureus compared with controls. Activated cells had more phagocytic activity and intracellular killing than normal macrophages. There were no differences in the viability of macrophage cells treated with extracts and those without extracts (control).